Amerasia - Horodowich, Elizabeth 1970-; Nagel, Alexander 1964- (Zone Books, 2023)
"This book explores the many ways in which European artists, writers, and cartographers described and represented an Amerasian continuum in the first two centuries after Columbus"--
Keywords: Blutiger Jupiter -- Musikgruppe -- Europa; Geschichte 1492-1700; Kartografie; Reisebericht; Darstellung; Kunst; Asien; Indien; Amerika; Geographical myths / Europe / History / 16th century; Geographical myths / Europe / History / 17th century; Asia / Description and travel / History / 16th century; Asia / Description and travel / History / 17th century; America / Description and travel / History / 16th century; America / Description and travel / History / 17th century; Amerasia; Mythes géographiques / Europe / Histoire / 16e siècle; Mythes géographiques / Europe / Histoire / 17e siècle; Asie / Descriptions et voyages / 16e siècle; Asie / Descriptions et voyages / 17e siècle; Amérique / Descriptions et voyages / 16e siècle; Amérique / Descriptions et voyages / 17e siècle; SOCIAL SCIENCE / General; Geographical myths